(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the problem of the differentiation of the Ukrainian official-business style. The position of investigating the structure of the style are analyzed, approach the domestic and foreign linguistics to its differentiation are considered.